Three universities and the British elite: a science of colonial administration in the UK - Dimier, Veronique (2006)
In this article we examine how the science of colonial administration, which evolved within the training for colonial administrators in the decades 1930-50 in Britain, became institutionalized in British Universities. We will see that both the colonial context and the somewhat ambivalent conception of colonial administration conveyed by academics such as Margery Perham, Lucy Mair and officials from the Colonial Office may have justified the need to consider colonial administration to be a scientific discipline in its own right, but that it was perhaps the fight between the universities to control and produce the British administrative elite which provided the driver that helped that science to gain institutional legitimacy. - Reproduced.
Keywords: Civil service - Great Britain; Civil service